2016
DOI: 10.1111/ijn.12495
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in climacteric Turkish women with urinary incontinence

Abstract: Urinary incontinence (UI) is a common health problem and negatively affects the quality of life of women who are afflicted. The aim of the study is to explore the prevalence and risk factors of UI among climacteric Turkish women and to examine the effects of UI on their quality of life. This cross-sectional study was conducted with 258 women aged 40-64 years who visited the outpatient clinic in Ankara, Turkey, between 15 June 2012 and 15 January 2013. The data were collected using the International Consultatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 29 publications
(58 reference statements)
2
19
1
2
Order By: Relevance
“…In other studies investigating the effect of UI on the quality of life, Akkuş et al found similar quality of life scores in women with UI, while Demirel et al found lower mean quality of life scores than in our study (Akkuş & Pınar, ; Demirel & Akın, ). In addition, Güvenç et al and Demirci et al found higher mean quality of life than in our study (Demirci et al, ; Güvenç, Kocaöz, & Kök, ). In two studies, it was found that the quality of life of all incontinent women decreased and that sexual problems increased (Caruso et al, ; Doğan, Vural, & Akyüz, ).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In other studies investigating the effect of UI on the quality of life, Akkuş et al found similar quality of life scores in women with UI, while Demirel et al found lower mean quality of life scores than in our study (Akkuş & Pınar, ; Demirel & Akın, ). In addition, Güvenç et al and Demirci et al found higher mean quality of life than in our study (Demirci et al, ; Güvenç, Kocaöz, & Kök, ). In two studies, it was found that the quality of life of all incontinent women decreased and that sexual problems increased (Caruso et al, ; Doğan, Vural, & Akyüz, ).…”
Section: Discussionsupporting
confidence: 54%
“…This study revealed relationships between UI and body image, self- (Demirci et al, 2012;Güvenç, Kocaöz, & Kök, 2016). In two studies, it was found that the quality of life of all incontinent women decreased and that sexual problems increased (Caruso et al, 2017;Doğan, Vural, & Akyüz, 2017).…”
Section: Discussionmentioning
confidence: 81%
“…When using the Incontinence Quality of Life Questionnaire in 787 Turkish women, the authors found that MUI and SUI had a greater effect on QoL compared to UUI (28) . Other authors emphasize that the presence of MUI has resulted in worse scores in most investigated domains (7,10,12,29) , and this same result was found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps because of stigma, this condition is associated with low rates of health care seeking (2) . In spite of that, studies show that approximately 12.4% of young women (3) , 45% of middle-aged and post-menopausal women (4) , and 75% of older women experience some involuntary urine loss (5) . In the United States, annual costs with routine care for UI management are estimated at US$ 50-1,000 per person (6) .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in a study by Zecca et al., approximately 35% of women reported that UI and its negative impact on quality of life was high. An investigation among perimenopausal women found that although the overall prevalence of UI was high (45.3%), few of the affected women sought medical treatment, which in turn had a serious impact on their quality of life. Dibiase et al .…”
Section: Discussionmentioning
confidence: 99%